Pengaruh Celebrity Endorser dan E-Wom Terhadap Minat Beli dengan Brand Image Sebagai Variabel Mediasi - Irmayanti Hasan; Adam Taufiqurrahman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of celebrity endorsers and electronic word of mouth on purchase intention with brand image as a mediating variable. This study uses primary data by distributing questionnaires to respondents via google form to collect research data. This study uses a non-probability sampling method combined with a purposive sampling method. Data analysis in this study used the SmartPLS version 4.0 application. The findings in this study indicate that celebrity endorsers have a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on brand image, celebrity endorsers have a positive and significant effect on purchase intention, electronic word of mouth has a positive and significant effect on purchase intention, brand image has a positive and significant effect on purchase intention. brand image can have a direct and significant effect on the relationship between celebrity endorser variables on purchase intention, brand image can have a direct and significant effect on the relationship between electronic word of mouth variables on purchase intention.